Determinants of Household-Level Water Treatment Practices in Southern Ethiopia - Daniel Sisay W/tsadik; Berhanu Gidisa Debela; Helen Ali Ewune; Habtamu Endashaw Hareru (SAGE Publishing, 2022)
Background: Household water treatment and handling is an important component of a global strategy to provide safe water to millions of people who live without adequate water currently. Household water treatment at the point of use also helps to improve drinking water quality for millions who suffer due to contamination of their drinking water. This study aims to assess household-level water treatment practices and associated factors in Southern Ethiopia. Methods: A community-based cross-sectional study was conducted among selected households using a systematical random sampling technique in Bule town. Data was collected using a pretested, structured questionnaire and analyzed using STATA version 16. A variable with a P -value ⩽ .25 in bi-variable regression was entered into multivariable regression and then a variable with a P -value ⩽ .05 was taken as statistically significant. Results: The study found that only 29.9% (with a 95% CI: 25.3-34.6) of households have good water treatment practices for drinking purposes. Regarding predictors of household-level water treatment practices, respondents who had good knowledge were 5 times (AOR = 6.98, 95% CI = 4.01-11.9) more likely to practice household-level water treatment than their counterparts. In addition, respondents who earn more than 3000 ETB per month are twofold more likely to practice household water treatment than those with an average monthly income of less than 1000 ETB (AOR = 2.37, 95% CI = 1.22-4.60). Conclusions: Household-level water treatment was less common in Bule town. The household's monthly income and their knowledge status were found to be the determinants of household-level water treatment practices in the study area.